RETRACTED: DA Negatively Regulates IGF-I Actions Implicated in Cognitive Function via Interaction of PSD95 and nNOS in Minimal Hepatic Encephalopathy - Ding, Saidan; Zhuge, Weishan; Wang, Xuebao; Yang, Jianjing; Lin, Yuanshao; Wang, Chengde; Hu, Jiangnan; Zhuge, Qichuan (Frontiers in Cellular Neuroscience, 2017)
Insulin-like growth factor I (IGF-I) has been found to be closely positively correlated with learning and memory ability. the cognitive decline in minimal hepatic encephalopathy (MHE) was reported to be induced by elevated intracranial dopamine (DA). The beneficial effect of IGF-I signaling in MHE remains unknown. In this study, we found the decrease in IGF-I in the MHE rats, and IGF-I administration improved the cognitive decline of MHE rats. A protective effect of IGF-Ⅰ on the DA-induced interaction between PSD95 and nNOS in neurons drives MHE pathology. RSK phosphorylates nNOS in response to IGF-I by recruiting the protein kinase ERK1/2. In turn, DA inactivates the ERK/RSK pathway and stimulates the PSD95–nNOS interaction by downregulating IGF-I. The inhibition of the interaction of PSD95 and nNOS ameliorated DA-induced memory impairment. As hallmarks of DA-induced deficits in the ERK/RSK pathway and the interaction of PSD95 and nNOS are present in MHE brains, treatment with IGF-I may exert beneficial effects by disruption of interaction of PSD95 and nNOS. These results suggested that IGF-I antagonized DA-induced cognitive loss by the disruption of the PSD95–nNOS interaction in MHE.